(untitled) (Proceedings of International Conference on Educational Discoveries and Humanities, 2024)
The purpose of this research is to determine the risk factors for otitis media, a common childhood illness in developing countries, especially Asia. The goal is to lower the prevalence of hearing loss and deafness in neonates by carrying out meticulously designed epidemiological research. In order to determine which preschool-aged children in a rural town had the highest prevalence of middle ear infections, the study examined the entire preschool-aged population. It was observed that 8.6% of research participants had a middle ear infection. The most common symptom was otitis media with effusion (OME), which was followed by eustachian tubal block (ETB). The study found several risk factors, such as mouth breathing and snoring, recurrent upper respiratory tract infections, seasonal rhinitis, and persistent rhinorrhea. These factors significantly raised the risk of getting a middle ear infection. However, sociodemographic variables like age, gender, and socioeconomic position did not show up as major risk factors in this rural group. The study highlights the importance of routine screening programs to identify and address risk factors, as well as the treatment of enlarged adenoids, chronic sinusitis, and underlying nasal sensitivities. Ads against smoking should especially emphasize the harm that passive smoking causes to minors’ otological and respiratory health.